Integrating Humanities into Cybersecurity Education: Enhancing Ethical, Historical, and Sociopolitical Understanding in Technical Training - Joseph Frusci (Journal of Cybersecurity Education, Research & Practice)
The increasing complexity of cybersecurity challenges necessitates a holistic educational approach that integrates both technical skills and humanistic perspectives. This article examines the importance of infusing humanities disciplines such as history, ethics, political science, sociology, law, and anthropology—into cybersecurity education. Through a pilot course developed for Staten Island Technical High School, aligned with the New York State K-12 Computer Science and Digital Fluency Standards, students were introduced to an interdisciplinary curriculum that combined technical cybersecurity training with historical analysis, ethical reasoning, and sociopolitical context. The results of pre- and post-course assessments demonstrated significant improvements in critical thinking, ethical decision-making, and the ability to evaluate cybersecurity issues from a broader societal perspective. This article discusses how an interdisciplinary approach not only enhances students’ technical competencies but also prepares them to address the ethical and societal dimensions of cybersecurity, making a case for incorporating humanities into the cybersecurity education curriculum at both secondary and post-secondary levels.